2014
DOI: 10.2495/esus140301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crude oil products on the geotechnical properties of soil

Abstract: Recently, the effects of crude oil on soil contamination have received a lot of attention from many researchers. Most of these researchers have studied the effect of crude oil itself without taking into consideration its products. Added to that, most of these outcomes have shown contradictions in their results due the addition of crude oil to the soil. Some results showed an increase in the maximum dry density while other results indicated a decrease. A similar trend was noticed in the shear strength of the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 4 publications
4
13
0
1
Order By: Relevance
“…In the present study, the sum of exchangeable cations, exchangeable capacity, and soil saturation with base cations were significantly diminished by DO and P. This effect was due to the negative impact of these products on, i.a., air-water properties [73,82,83]. According to Rasheed et al [84], soil pollution with DO and P may cause the loss of their elasticity and viscosity. In turn, Prasanna and Manoharan [85] ascribe this unfavorable effect to a greater pool of physical and chemical parameters changing in soil upon its pollution with these products.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the sum of exchangeable cations, exchangeable capacity, and soil saturation with base cations were significantly diminished by DO and P. This effect was due to the negative impact of these products on, i.a., air-water properties [73,82,83]. According to Rasheed et al [84], soil pollution with DO and P may cause the loss of their elasticity and viscosity. In turn, Prasanna and Manoharan [85] ascribe this unfavorable effect to a greater pool of physical and chemical parameters changing in soil upon its pollution with these products.…”
Section: Discussionmentioning
confidence: 99%
“…Other scientists mention that the internal friction angle, unconfined compression strength, specific gravity of solids, cohesion and Atterberg limits decrease in the presence of diesel, but pH increases [9,11,16,19,20]. However, there are some authors that report other behaviors; for example, Atterberg limits are increased in the presence of diesel [22], and the internal friction angle is increased in the presence of kerosene and gas oil [15]. All authors show up the importance to keep doing investigations, and for that reason this study seeks to determinate the changes and effects in the mineralogy composition and geotechnical properties of clay soil by the presence of diesel, and there is a special contribution to analyze the effect of the test temperature because if the diesel presence is unknown the temperature is 110 ± 5 °C but 50 ± 5 °C, it has not been researched.…”
Section: Introductionmentioning
confidence: 99%
“…Salih et al found that UMO not only increases the PL but also LL and PI [38]. Rasheed et al reported that Atterberg's value of overconsolidated clay decreases by increasing UMO contents [11]. LL and PL decrease by increasing UMO contents [19,27].…”
Section: Atterberg's Limit Testmentioning
confidence: 99%
“…Researchers such as Evgin et al, Khamehchiyan et al, and Ukpong et al studied the changing behavior of soil by considering the effects of crude oil [8][9][10]. Rasheed et al demonstrate that the PL and LL increase, while MDD and OMC decrease with the increase in oil percentage as an additive in soil [11]. e behavior of motor oil on cohesion and CBR was studied by Nazir who stated that cohesion decreases while the angle of internal friction v increases with an increase in the tendency of motor oil in soil [12].…”
Section: Introductionmentioning
confidence: 99%